Navigating African Maritime History. - Ray, Carina E. (Research in Maritime History LUP., 2017)
This book is a collection of essays addressing multiple aspects of African maritime history in attempt to counter the lack of academic research that exists in comparison to other nations and continents, and to assert the value of African topics to the global study of maritime history.